I solving the inverse Laplace transform using the method of Heaviside. This is part of the problem:

enter image description here

I understand the division between complex numbers and that $e^{it} = Cos(t) + iSin(t)$, but I got stuck in the third row.I developed the product but I don't quite understand how it came to $-Cos(t)+ \frac{1}{2}Sin(t)-Cos(t)+ \frac{1}{2}Sin(t)$


I'm not entirely sure which step is confusing you. So starting from:

$$=\cfrac{4}{2} e^t + \cfrac{3i+1}{-2-2i} e^{it} + \cfrac{-3i+1}{-2+2i}e^{-it}$$

As you noted, the next step is simply just the division of complex numbers

$$\cfrac{3i+1}{-2-2i}=\cfrac{3i+1}{-2-2i}\cfrac{-2+2i}{-2+2i}=\cfrac{-4i-8}{8}=(-1-1/2 i)$$

$$\cfrac{-3i+1}{-2+2i}=\cfrac{-3i+1}{-2+2i}\cfrac{-2-2i}{2-2i}=\cfrac{4i-8}{8}=(-1+1/2 i)$$

And the fact that $e^{it} = \cos{t}+i\sin{t}$, $e^{-it}=\cos{t}-i\sin{t}$.

Thus $$\begin{aligned} &=2e^t + (-1-1/2i)(\cos{t} + i\sin{t}) + (-1+1/2i)(\cos{t}-i\sin{t})\\ &=2e^t - \cos{t}-i\sin{t} -1/2 i \cos{t} +1/2\sin{t} -\cos{t}+i\sin{t} +1/2i \cos{t} +1/2\sin{t}\\ &=2e^t-2\cos{t}+\sin{t} \end{aligned}$$

The last step simplifies a lot because we note that all the $a i \sin{t}$ and $b i \cos{t}$ terms cancel out.

  • $\begingroup$ Oh such a dumb mistake! Now I see haha Thanks! $\endgroup$ – Sandra Torres Jun 5 '16 at 20:26

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.